1999
DOI: 10.1042/0264-6021:3430525
|View full text |Cite
|
Sign up to set email alerts
|

The role of tyrosine-9 and the C-terminal helix in the catalytic mechanism of Alpha-class glutathione S-transferases

Abstract: Glutathione S-transferases (GSTs) play a key role in the metabolism of drugs and xenobiotics. To investigate the catalytic mechanism, substrate binding and catalysis by the wild-type and two mutants of GST A1-1 have been studied. Substitution of the 'essential' Tyr(9) by phenylalanine leads to a marked decrease in the k(cat) for 1-chloro-2,4-dinitrobenzene (CDNB), but has no affect on k(cat) for ethacrynic acid. Similarly, removal of the C-terminal helix by truncation of the enzyme at residue 209 leads to a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
54
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 20 publications
2
54
1
Order By: Relevance
“…The k Ϫ2(exp) could not be determined directly, presumably because GS-EA binds too tightly and is not displaced by the trapping agent, GSO 3 Ϫ . Surprisingly, in steady state reactions with hGST A1-1 and EA, k cat was unchanged upon substitution at Tyr-9, in contrast to our results, which suggest a decreased k cat for a Y9F-catalyzed reaction, which is rate-limited by product release (24). The source of these differences is unknown.…”
Section: Resultscontrasting
confidence: 56%
See 3 more Smart Citations
“…The k Ϫ2(exp) could not be determined directly, presumably because GS-EA binds too tightly and is not displaced by the trapping agent, GSO 3 Ϫ . Surprisingly, in steady state reactions with hGST A1-1 and EA, k cat was unchanged upon substitution at Tyr-9, in contrast to our results, which suggest a decreased k cat for a Y9F-catalyzed reaction, which is rate-limited by product release (24). The source of these differences is unknown.…”
Section: Resultscontrasting
confidence: 56%
“…A similar effect was observed in equilibrium binding studies with Y9F hGST A1-1. Allardyce et al (24) recently found that Y9F hGST A1-1 binds the ligand, S-dinitrophenylglutathione, 20-fold more tightly than WT. ⌬H°and ⌬S°values also indicate a difference in the thermodynamics of binding to each enzyme.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the mechanistic investigations of GSTs have emphasized the importance of a conserved tyrosine or serine residue at the glutathione binding site of certain GSTs (Tyr-8 for Pi, Tyr-9 for Alpha, Tyr-6 for Mu, and Ser-9 for Delta class) in facilitating the thiol deprotonation (10,(21)(22)(23). The hydroxyl group of this tyrosine or serine residue that is within hydrogenbonding distance of the thiol group of enzyme-bound glutathione is considered to be required for the correct orientation and stabilization of the deprotonated thiolate anion in the active site (10, 22, 24 -26).…”
mentioning
confidence: 99%